Pre-Descemets endothelial keratoplasty: the PDEK clamp for successful PDEK - Dua, H S (Eye (Lond), 2017)
PURPOSE: To design and produce a clamp that enables good handling of donor sclera-corneal disks, allows air to be injected in the corneal stroma and consistently provides pre-Descemets endothelial keratoplasty (PDEK) tissue by creation of a type-1 big bubble (BB) avoiding a type-2BB by shutting the fenestrations in the periphery of the pre-Descemets layer and preventing escape of air. PATIENTS AND METHODS: A clamp with spring loaded handles attached to two rings of 9 mm diameter and 1 mm width with a side port for insertion of a needle for air injection was designed and produced. The clamp was tested in 20 human donor sclera-corneal disks and refined over three prototypes. The final design was used for PDEK in 8 patients. RESULTS: The clamp was able to prevent any escape of air or the formation of a type-2BB. By preventing air leak, it provided better control over the volume of air injected allowing for consistent formation of a type-1BB, which could be expanded to its full diameter by advancing the tip of the needle into the bubble cavity. Centration of tissue in the clamp was important. The clamp was used successfully to obtain PDEK tissue from 8 donor sclara-corneal disks for transplant in three eyes with pseudophakic bullous keratopathy and five eyes with pseudophakia and Fuchs’ endothelial dystrophy. CONCLUSION: The PDEK clamp is a simple and useful instrument that will give surgeons the confidence of consistently obtaining PDEK tissue with ease and without the risk of separating the Descemets membrane in a type-2BB.